Rentability of Livestock Bussiness of Batur Sheep at Banjarnegara Regency - S. B. Manik; S. I. Santosa; W. Sumekar (Jurnal Ilmu dan Teknologi Peternakan, 2015)
This research aimed to evaluate the profit and rentability of livestock business of Batur sheep at Banjarnegara Regency. The research was carried out using survey method involving 120 Batur sheep breeder as samples. The data used in this study were primary and secondary data.The data were analyzed descriptively. The research results indicated that average of production cost was IDR. 3,574,776.66; the average income was IDR. 6,994,654.17; the profit was IDR. 3,419,877.51; and the average of financial capital was IDR. 8,985,771.94, giving the rentabilityof business to be 38.08%. The average age of Batur sheep breeder was between 31 and 40 years old; the level of education was mostly elementary school, which was as much as 79.17%. The occupancy of the breeder was dominated by farmer, which was as high as 80.83%. The percentage of breeders having average farming experience between 6-10 years was around 54.17%.